You Are the Father! Engaging Non-Custodial Black Fathers in Parenting Utilizing Critical Historical Policy Analysis and Ecological Systems Theory - Cole, Amber; Lipscomb, Allen (Journal of Social Work Education and Practice, 2023)
The “Buck” or “Rapper” stereotype serves as a trope that depicts Black/African American fathers as a fearful, criminal, no good, drug slanging pimps---not as loving and engaged fathers. These historical images, narratives are further supported through policies and de facto practices that continue to create racist barriers for Black fathers to fully be involved in child rearing practices. Thus, this article will explore through a critical lens the historical policies and racist practices that continue to impact Black fathers utilizing an ecological systems theoretical framework. In addition, this article will propose a policy action plan whereby creating new policies that are just, equitable and antiracist.
Keywords: noncustodial; Black fathers; ecological systems theory; policy analysis